PENERAPAN PELAPORAN SPT MASA PPN MENGGUNAKAN E-SPT PPN TERHADAP WAJIB PAJAK DITINJAU DARI PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Hiong, Lauw Sun (MABIS, 2012)
At this time the role of technology in human life and activity to carry out the work or solvethe problems they faced, has a very big role. System change from manual to computerized system that uses technology to process data into an information, will have a very big problem if the user does not have experience in the receiving culture and technology in the lives of their activities. E-SPT application is an application provided by the Director General of Taxation which can be used by the taxpayer to facilitate in making and reporting every month or year. The topics that will be discussed on the E-PPN SPT Masa. The main purpose of this application to answer and respond to the increasing needs and improve service to the taxpayer in terms of tax reports processing cost savings, especially the cost of paper or printing which has a high percentage of operating costs weighed on the company. To find out how much the individuals perception of using technology can be in the review of the technology acceptance model or commonly called the Technology Accepted Model (TAM). This model can be used to predict user acceptance of the new technology. The model introduced by Fred D. Davis in 1989 is the most widely used models in information systems research, because it produces good validity.